Peroxisomal lipid metabolism inhibits Pimozide-induced cancer cell death by regulating ATP homeostasis - Zihang Pan; Fazhi Yu; Weiyi You; Feng Li; Fengjuan Cui; Jing Guo; Zhenye Yang (Oncogenesis)
Abstract Antipsychotic drugs have been shown to suppress tumor growth and induce cell death, but their clinical application remains limited. Pimozide, an FDA-approved antipsychotic, holds significant potential for cancer treatment. However, the mechanisms underlying tumor cell responses to Pimozide remain unclear. In this study, we identify a critical role for peroxisomes in mediating tumor cell resistance to Pimozide. Our findings demonstrate that Pimozide increases peroxisome numbers and that peroxisomal deficiency significantly enhances Pimozide-induced cell death. We show that peroxisomes mitigate Pimozide-induced apoptosis primarily through fatty acid oxidation and ether lipid synthesis, rather than reactive oxygen species (ROS) metabolism. Moreover, Pimozide treatment upregulates peroxisomal lipid-metabolizing enzymes in tumor cells. As key metabolic hubs interconnected with mitochondrial metabolism, peroxisomes support energy homeostasis, thereby preventing Pimozide-induced cell death. These findings underscore the importance of peroxisomes in maintaining mitochondrial morphology and cellular energy homeostasis, offering novel insights into the potential therapeutic applications of Pimozide in cancer treatment.